Analisis Kualitas Minyak Nilam (Pogostemon cablin Benth) Produksi Kabupaten Buol - Ahmad Idris; Minarni Rama Jura; Irwan Said (Universitas Tadulako, 2014)
Patchouli ( pogostemon cablin benth ) is one of the essential oil producing plants which are quite important, known as Oil Patchouly. This oil pick strategic potential in the world market which is used as a binder fragrance in perfumes, cosmetics, pharmaceutical industry, and other industries. Buol which aims to determine the quality of patchouli oil. Samples is patchouli oil yield Buol. Parameters in meticulous ie specific gravity, refractive index, acid Numbers, Numbers Esther, and Solubility in Alcohol. The technique used is the technique of sampling area. The results showed that the Weighted Value Type 25oC / 25°C for samples A = 0.997 to 1.000, B = 0.962 to 0.965, C = 0.995 to 0.998 D = 0.980 to 0.983, and E = 0.968 - 0.971. To value Bias Index ( nD20 ) ie sample A = 1.45505 to 1.45705, B = 1.45506 to 1.45706, C = 1.45504 to 1.45704, D = 1.45503 to 1.45703, and E = 1.45523 to 1.45723. Numbers for acid sample value A = 2.805, B = 3.366, C = 2.5245, D = 3.0855 and E = 3.6465. For esther numbers are sample values A = 15.4275, B = 5.61, C = 12.6225, D = 4.2075 and E = 19.635. And last is the determination of solubility in alcohol that sample A = 1 : 2, B = 1 : 1.7, C = 1 : 0.9, D = 1 : 1, and E = 1 : 3. These data show patchouli oil production Buol area has good quality in terms of acid value, ester number and solubility in alcohol is the average Indonesian National Standards meet the standards and ISO. While the specific gravity and refractive index still does not meet the Indonesian National Standard and ISO.